Clinical profile of scrotal swellings in Jharkhand, India: our experience of four rural health camps - Munda, Vishnu Singh; Murmu, Nagendra Nath; Kumar, Sanjeev; Bhengra, Ajay; Korah, Manoj Kumar; Kumar, Rakesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Scrotal swellings are one of the common problems in all age groups. Since these swellings are usually painless and can attain a very big size without causing much discomfort; the patients are reluctant to seek medical advice. Social stigma, embarrassment and fear of getting under the knife are the other reasons for late presentation. However in developing countries like India; the poverty, illiteracy, unawareness and poor health care facilities are the common reasons for late presentation. The objective of the study was to bring forward the volume of problem and morbidity associated with scrotal swellings in rural populations of Jharkhand, India. Methods: This study was based on the four health camps with emphasis on scrotal swellings organized in the rural areas East Singhbhum, West Singhbhum and Simdega districts of Jharkhand state in Eastern India between December 2015 and June 2017. Data obtained from these camps were analyzed retrospectively. Results: A total of 1567 persons were screened for scrotal swellings in four camps; 180 (11.4%) of them found to have some scrotal pathology. Most of the cases were in the age group of 31-50 years (61.35%), scrotal swelling being main complaint. Out of the 180 cases with scrotal swelling, Primary vaginal hydrocoele was found in 78.9% (n=142); followed by sebaceous cyst and epididymal cyst. The majority of cases had symptom duration of 1 to 2 years– 33.9% (n=61), followed by 2 to 5 years– 23.23% (n=42); the duration of symptoms ranged from 2 weeks to 12 years. Conclusions: Although the diagnosis and treatment of scrotal swellings are relatively simple the number of patients with scrotal swellings is high, especially in the rural areas of developing countries like India. The rural health camps can be effective in decreasing the morbidities of scrotal swellings.